Toxicity Evaluation of Treated Refinery Effluent using brine Shrimp (Artemia salina) Egg and Larval Bioassay - P.K., Krishnakumar; A.P., Dineshbabu; Sasikumar, Geetha; G.S., Bhat (Fishery Technology, 2025)
A bioassay test using Artemia Salina egg and larvae is conducted to evaluate the aquatic toxicity treated refinery effluents. The brine shrimp (Artemia salina) has gained popularity as test organism for short-term toxicity testing because of its ease of culture, short generation time, cosmopolitan distribution and its commercial availability as dormant eggs. One year study has been carried out to assess toxicity of effluent samples collected from an oil refinery at Mangalore, (India) on the egg hatching and larval survival rate of A. salina. The chemical quality of the refinery effluent collected during Oct 2002 - Sep 2003 was found to be within the prescribed permissible limits. The mean EC50 for egg hatching rate using the effluent collected during the dry and wet seasons was 40.6% and 73.4% effluent (% by volume) respectively. The mean LC50 value for larval mortality using the effluent samples collected during the dry and wet seasons was 37.2% and 48% effluent respectively. The mean No Observed Effect Concentration (NOEC) for the effluent in the present study was 6.3%. The reported natural dilution available in the Arabian Sea near the marine outfall of the refinery is sufficient enough to dilute the effluent below the observed NOEC.